ANALISIS NILAI PENDIDIKAN KARAKTER PADA BUKU DONGENG DAN CERITA RAKYAT UNTUK SISWA SEKOLAH DASAR - Prastiwi, Krismon; Sudigdo, Anang Sudigdo (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2022)
This study aims to describe the values ​​of character education in fairy tales and folklore books. This research is descriptive qualitative research using the research librarian method or literature study by analyzing some of the contents of a collection of fairy tales and folklore books. The research procedure in this thesis includes the preparation stage, implementation stage, and completion stage. The source of the research data is in the form of a collection of fairy tales and folklore books. The data collection technique uses non-participant observation and documentation techniques. The data validity technique in this study used the observation extension technique, increasing persistence, and triangulation. The results of this study indicate that: from the six fairy tales and folklore found results that in the titles "The Origin of Lake Toba", "Onions and Garlic", "Puteri Niwer Gading", "Kind-hearted Kings", and "Malin Kundang contains five (5) character education values, namely religious, nationalism, integrity, independence, and cooperation. The story entitled "The Legend of the Crying Stone" contains four (4) values ​​of character education including religion, integrity, independence, and cooperation. Both fairy tales and folklore can be used as a medium to instill character values ​​so that students can apply them in everyday life.